Synthesis of Sodalite Zeolite and Adsorption Study of Crystal Violet Dye. (1st October 2019) - Klunk, Marcos; Dasgupta, Sudipta; Das, Mohuli; Cunha, Marcelo Gregory; Wander, Paulo Roberto
Abstract : Application of efficient technologies is imperative to minimize the impact of textile effluents on the environment. A solution to this problem is the application of molecular sieves such as zeolites. The sodalite zeolite has structural characteristics that allow its application as an adsorbent of heavy metals and chromophoric groups, responsible for coloring the clothing fabric. The objective of this work was to synthesize and evaluate the application of sodalite zeolite with four Si/Al ratios (1.0, 1.5, 2.0 and 2.5), using organic template. X-ray diffraction exhibits the crystalline phases of sodalite zeolite, marking the presence of minerals like kaolinite, mullite and quartz. Cation-exchange-capacity is 37% more in case of 2.5-SOD zeolite, compared to that of 1.0-SOD in the zeolitization process. The dye adsorption process was efficient at low concentrations (5, 10 and 25 mg/L) of the textile dye than higher concentrations (50, 75 and 100 mg/L) of the dye and hence, determining the concentration of the dye was of fundamental importance for efficiency regarding color removal. Therefore, it can be concluded that the synthesized sodalite zeolites (with low concentrations) in our study have substantial success potential in the effective removal of dyes from the textile industry.